Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
Đặt A = 1/2+(1/2)2+(1/2)3+...+(1/2)109+(1/2)110
=> 2A = 1 + 1/2+(1/2)2+(1/2)3+...+(1/2)109
=> 2A - A = 1 - \(\frac{1}{2^{110}}\)
=> A = 1 - \(\frac{1}{2^{110}}\)
Ta có : \(\frac{1}{2^2}+\frac{1}{3^2}+\frac{1}{4^2}+...+\frac{1}{1990^2}=\frac{1}{2.2}+\frac{1}{3.3}+\frac{1}{4.4}+...+\frac{1}{1990.1990}\)
\(< \frac{1}{2.2}+\frac{1}{2.3}+\frac{1}{3.4}+...+\frac{1}{1989.1990}=\frac{1}{4}+\frac{1}{2}-\frac{1}{3}+\frac{1}{3}-\frac{1}{4}+...+\frac{1}{1989}-\frac{1}{1990}\)
\(=\frac{1}{4}+\frac{1}{2}-\frac{1}{1990}=\frac{3}{4}-\frac{1}{1990}< \frac{3}{4}\left(\text{đpcm}\right)\)
Bài làm :
Ta có :
\(\frac{1}{2^2}+\frac{1}{3^2}+\frac{1}{4^2}+...+\frac{1}{1990^2}\)
\(=\frac{1}{2.2}+\frac{1}{3.3}+\frac{1}{4.4}+...+\frac{1}{1990.1990}< \frac{1}{2.2}+\frac{1}{2.3}+\frac{1}{3.4}+...+\frac{1}{1989.1990}=\frac{1}{4}+\frac{1}{2}-\frac{1}{3}+\frac{1}{3}-\frac{1}{4}+...+\frac{1}{1989}-\frac{1}{1990}=\frac{1}{4}+\frac{1}{2}-\frac{1}{1990}=\frac{3}{4}-\frac{1}{1990}\)
\(\text{Vì : }\frac{1}{1990}>0\Rightarrow\frac{3}{4}-\frac{1}{1990}< \frac{3}{4}\)
=> Điều phải chứng minh
Ta có : \(A=\frac{1}{2}+\frac{1}{2^2}+\frac{1}{2^3}+.....+\frac{1}{2^{110}}\)
\(\Leftrightarrow2A=1+\frac{1}{2}+\frac{1}{2^2}+....+\frac{1}{2^{109}}\)
\(\Leftrightarrow2A-A=1-\frac{1}{2^{110}}\)
\(\Leftrightarrow A=1-\frac{1}{2^{110}}< 1\)